Ratings of Universities 2: Search for a paradigm of higher education against the background of the global crisis and balkanization - Lidin, Konstantin (project baikal, 2015)
During the period between the fall of the Iron Curtain (1986) and the beginning of the global crisis (2008) Russian universities made an attempt to switch over to graduation of specialists that would be able to meet competition in the international market for intellectual labour. As the crisis evolved, the processes of globalization of higher education in Russia faced problems of the bureaucratized system of management. As a result, Russian universities split up into two unequal groups: the minority of universities remained on the way of globalization and integration into the global system, and the majority (about 95 %) took a track of balkanization. The architecture of university campuses is expected to develop in two directions: one of them is in line with international stylistics common for all regions of the world, and the other keeps with diversity of regional and situational decisions tied to peculiarities of a certain university.
Keywords: University; architecture; campus; globalization; balkanization